Po co tak się męczyć? Czynniki motywujące do aktywności w klubach fitness. Komunikat z badań = Why shall one get so much tired? Motivating factors for physical activity in fitness clubs. Research results - Bazuń, Dorota (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The objective of the article is to answer the question about the sources of motivation in case of physical activity in fitness clubs. It takes a great organizational, financial and physical effort to participate in this kind of activities. What makes people choose physical activity instead of simpler laziness in front of the TV? When do they prefer individual and when group exercises? Participants` motivations are varied - most often they are connected with their desire to keep fit and loose weight.
Keywords: motywacja; aktywność fizyczna; fitness